Exploring Trends of Organizational Citizenship Behavior (OCB) Studies for Future Research: A Bibliometric Analysis - Josafat Gracia Ginting; Ikram Muhaidir; Mufidatul Azmi (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: The objectives of this study are to analyze research trends in OCB, identify research gaps, and examine author collaboration patterns to understand the intellectual structure of OCB research. Research Method: This study employs a quantitative bibliometric approach to examine the development of research on Organizational Citizenship Behavior (OCB). A total of 300 articles published between 2021 and 2026 were retrieved from the ScienceDirect database and analyzed using VOSviewer to map co-authorship and co-occurrence networks. Results and Discussion: The findings indicate that: (1) Recent OCB research increasingly integrates psychological factors with organizational sustainability concerns; (2) future research should integrating OCB determinants across four key pillars namely leadership style, employee work attitudes, employee occupational health, and organizational policies; and (3) the analysis of author collaboration reveals the dominance of four major author clusters that collectively shape the intellectual structure of OCB research during the analyzed period. Implications: The findings suggest that organizations should integrate strategic policies, such as Green HRM and ethical leadership, to encourage employees' voluntary behaviors effectively. Furthermore, this bibliometric mapping suggests that future research should explore untapped areas such as energy transition and informal learning.